MRI findings of granulomatosis with polyangiitis can mimic those of cholesteatoma: A case report - Lubna Alkattan; Margaret Duraj; Daiva Erentaite; Yousef Yavarian (Radiology Case Reports)
Middle ear diseases are a common problem encountered by both general practitioners and otolaryngologists; the symptoms include pain, discharge, fever, and hearing loss. Common initial diagnoses include acute and chronic otitis media, cholesteatoma, and necrotizing otitis. Granulomatosis with polyangiitis is a rare autoimmune disease characterized by necrotizing vasculitis and granulomatous inflammation that affects the small- and medium-sized vessels of the upper and lower respiratory tracts, kidneys, and other organs. Furthermore, manifestations of granulomatosis with polyangiitis in the middle ear and temporal bone are highly unexpected. The more severe cases involve infection in the surrounding soft tissue, such as ear canal abscess and involvement of the temporal bone called osteomyelitis. In such cases the symptoms can involve vertigo, facial palsy, and systemic infection. Herein, we report a case of a 17-year-old girl with a history of left-sided chronic otitis media who was unresponsive to the usual treatment and presented with dizziness and left-sided peripheral facial paresis. Physical examination revealed a significant left-sided conductive hearing loss and left-sided persistent peripheral facial palsy, along with IX-XI cranial nerve palsies. We found initial diffusion restriction on diffusion-weighted imaging sequences of magnetic resonance imaging, which mimics cholesteatoma and middle ear abscess. Early diagnosis of granulomatosis with polyangiitis enables timely treatment with immunosuppressive therapy, thereby preventing the occurrence of late complications. Therefore, radiologists must be aware of these magnetic resonance imaging findings in patients with otitis media who are unresponsive to usual treatment, with or without facial palsy. Through this case report, we aim to highlight granulomatosis with polyangiitis as an additional differential diagnosis of cholesteatoma.